Bit-Error Aware Lossless Color Image Compression - Peng, Xuan; Hou, Jintao; Tan, Lizhe; Chen, Jungan; Jiang, Jean; Guo, Xinnian (IEEE International Conference on Electro Information Technology, 2019)
In this paper, we propose bit-error aware lossless compression algorithms for color image compression subject to bit-error rate during transmission. Each of our proposed algorithms contains three stages. The first stage converts the RGB images to YCrCb images. The next stage uses the predictive encoder to generate the residue sequence. A genetic algorithm is adopted to search the best combination of the color transformation and prediction. At the last stage, the generated residue sequence by predictive coding is encoded. Three residue encoding methods are investigated, including bi-level block coding, or interval Huffman coding or Huffman coding. To protect the bit stream from bit errors during transmission, (7,4) Hamming code is used to protect the color transformation information, predictor type and parameters, and residue coding parameters. Our experimental results validate the coding performances in terms of the compression ratio (CR) and peak signal to noise ratio (PSNR).